2015
DOI: 10.5123/s1679-49742015000200011
|View full text |Cite
|
Sign up to set email alerts
|

Problema crônico de coluna e diagnóstico de distúrbios osteomusculares relacionados ao trabalho (DORT) autorreferidos no Brasil: Pesquisa Nacional de Saúde, 2013

Abstract: Objetivo: descrever a prevalência de problemas crônicos de coluna e de distúrbios osteomusculares relacionados ao trabalho (DORT) autorreferidos em adultos brasileiros, segundo variáveis sociodemográficas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
27
0
34

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(68 citation statements)
references
References 20 publications
7
27
0
34
Order By: Relevance
“…21,22 Regarding age, we observed that, in most of the studies analyzed spine pain is a condition directly proportional to the age of the individual affected, i.e., it increases with age. 13,21 This may be related to the fact that in the natural human aging process people become more fragile and vulnerable to spine pathologies, causing changes in lifestyle and making them generally more dependent when performing life activities. 23 In this study, the color or race variable was not associated with the prevalence of spine pain among Brazilians.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 Regarding age, we observed that, in most of the studies analyzed spine pain is a condition directly proportional to the age of the individual affected, i.e., it increases with age. 13,21 This may be related to the fact that in the natural human aging process people become more fragile and vulnerable to spine pathologies, causing changes in lifestyle and making them generally more dependent when performing life activities. 23 In this study, the color or race variable was not associated with the prevalence of spine pain among Brazilians.…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, chronic back problems are also one of the most frequent chronic conditions in the population, with prevalence in adults 18 years or older of 18.5% (95%CI: 17.8-19.1), according to data from the Brazilian National Health Survey (PNS) in 2013 12 . Chronic back problems in the PNS are selfreported (not requiring a medical diagnosis), specifying the location (neck, lumbar area, vertebrae/ discs) and including pain in the definition of chronicity.…”
Section: Introductionmentioning
confidence: 99%
“…Ou seja, resultam de problemas relacionados diretamente ao local de trabalho 11,12 . Essas patologias afetam a qualidade de vida do indivíduo na realização de suas atividades cotidianas e geram impactos socioeconômicos negativos por ocasionarem limitações e incapacidades relacionadas ao trabalho 13 . A implementação de ações em saúde específicas, voltadas ao ambiente de trabalho, pode ser uma forma de prevenção e de se evitar o afastamento do indivíduo 14 .…”
Section: ▄ Introduçãounclassified